Buoyant Densities and Dry-Matter Contents of Microorganisms: Conversion of a Measured Biovolume into Biomass - Bakken, Lars R. (1983)
Several isolates of bacteria and fungi from soil, together with cells released directly from soil, were studied with respect to buoyant density and dry weight. The specific volume (cubic centimeters per gram) of wet cells as measured in density gradients of colloidal silica was correlated with the percent dry weight of the cells and found to be in general agreement with calculations based on the partial specific volume of major cell components. The buoyant density of pure bacterial cultures ranged from 1.035 to 1.093 g/cm(3), and their dry-matter content ranged from 12 to 33% (wt/wt). Average values proposed for the conversion of bacterial biovolume into biomass dry weight are 1.09 g/cm(3) and 30% dry matter. Fungal hyphae had buoyant densities ranging from 1.08 to 1.11 g/cm(3), and their dry-matter content ranged from 18 to 25% (wt/wt). Average values proposed for the conversion of hyphal biovolume into biomass dry weight are 1.09 g/cm(3) and 21% dry matter. Three of the bacterial isolates were found to have cell capsules. The calculated buoyant density and percent dry weight of these capsules varied from 1.029 g/cm(3) and 7% dry weight to 1.084 g/cm(3) and 44% dry weight. The majority of the fungi were found to produce large amounts of extracellular material when grown in liquid cultures. This material was not produced when the fungi were grown on either sterile spruce needles or membrane filters on an agar surface. Fungal hyphae in litter were shown to be free from extracellular materials.